Efficient method for iodine radioisotope labeling of cyclooctyne-containing molecules using strain-promoted copper-free click reaction. Issue 13 (1st July 2015) - Jeon, Jongho; Kang, Jung Ae; Shim, Ha Eun; Nam, You Ree; Yoon, Seonhye; Kim, Hye Rim; Lee, Dong Eun; Park, Sang Hyun
Graphical abstract: Abstract: Herein we report an efficient method for iodine radioisotope labeling of cyclooctyne-containing molecules using copper-free click reaction. For this study, radioiodination using the tin precursor2 was carried out at room temperature to give 125 I-labeled azide ([ 125 I]1 ) with high radiochemical yield (85%) and excellent radiochemical purity. Dibenzocyclooctyne (DBCO) containing cRGD peptide and gold nanoparticle were labeled with [ 125 I]1 at 37 °C for 30 min to give triazoles with good radiochemical yields (67–95%). We next carried out tissue biodistribution study of [ 125 I]1 in normal ICR mice to investigate the level of organ accumulation which needs to be considered for pre-targeted in vivo imaging. Large amount of [ 125 I]1 distributed rapidly in liver and kidney from bloodstream and underwent rapid renal and hepatobiliary clearance. Moreover [ 125 I]1 was found to be highly stable (>92%) in mouse serum for 24 h. Therefore [ 125 I]1 could be used as a potentially useful radiotracer for pre-targeted imaging. Those results clearly indicated that the present radiolabeling method using copper free click reaction would be quite useful for both in vitro and in vivo labeling of DBCO group containing molecules with iodine radioisotopes.